Pengaruh Keadilan, Perilaku, Persepsi Penerapan Undang-Undang Harmonisasi Peraturan Perpajakan Terhadap Kepatuhan Wajib Pajak - Puji Rahayu; Imarotus Suaidah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
Changes in tax regulations that often change make people less understanding. This change is also felt by MSME taxpayers. Initially, the MSME tax was regulated in PP 46 of 2013, which was amended by PP 23 of 2018, and lastly was amended by the HPP Law. This relatively short change has given rise to various perceptions by MSMEs. There is a perception that there is no aspect of justice in the indications that the behavior of taxpayers tends to not comply with these regulations. So the researcher wants to raise this issue for research. The purpose of this study was to determine the effect of justice, behavior and perceptions of the ease of implementing the HPP Law on MSME taxpayer compliance in the city of Kediri in 2022. This study used quantitative research. The data source used is primary data. The sampling method used purposive sampling. The data analysis technique used is SPSS with multiple linear regression analysis method. The results showed that partially fairness had a significant positive effect on taxpayer compliance. Taxpayer behavior and perception of convenience have no effect on taxpayer compliance. However, simultaneously justice, behavior, and perception of convenience affect taxpayer compliance. The implication of this research is for tax officers to provide assistance to WP UMKM. So that MSMEs appear to have a positive perception of justice and behave by paying taxes on time.